Aplikasi Response Surface Methodology (RSM) dengan Historical Data pada Optimasi Proses Produksi Burger - Mawi Prabudi; Budi Nurtama; Eko Hari Purnomo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
Customer satisfaction is a key for an industry because with high grade level satisfaction then expected customer will be loyal to the product and can be loyal customer. Good product quality is a manufacturer that is very concerned about the quality of the product. The enhancement of burger production can be seen from 2014 to 2015, that is 7.12%, then increased by 22.79% in 2016 than 2014. Burger production processes include incoming material, weighing, grinding, raw material mixing, input mixing material to the casing (filler), cooking, cooling, cutting by size, packaging, checking using metal detector, freezing, cold storage, and distribution. On this research used historical data, where the data used is data taken through direct observation with record all data and parameters measured. The data used is as much as 50 data with using 3 factors : speed, diameter and temperature. While the desired response is thickness of product (thick) of 4mm, weight of product (weight) of 14g, bubble (on scale 1-3) maximum on scale 2 and defect (disability product) maximum 5%. The optimum burger production obtained by using Design Expert-7 (DX-7) is at condition 243 rpm speed, 7 cm product diameter, and 11.6 C temperature. This can be proved by the verification result indicating that the thick value of 3.825 mm; weight 14.105 g; bubble on a scale of 2 and the defect is in the range of 4.41%, which means that the overall verification results are in the range of 95% CI low and 95% CI high. This shows that the modeling results of software used can be applied to the daily production of burger products in order to obtain optimal results.